2021
DOI: 10.3390/w13040406
|View full text |Cite
|
Sign up to set email alerts
|

The Seagrass Holobiont: What We Know and What We Still Need to Disclose for Its Possible Use as an Ecological Indicator

Abstract: Microbes and seagrass establish symbiotic relationships constituting a functional unit called the holobiont that reacts as a whole to environmental changes. Recent studies have shown that the seagrass microbial associated community varies according to host species, environmental conditions and the host’s health status, suggesting that the microbial communities respond rapidly to environmental disturbances and changes. These changes, dynamics of which are still far from being clear, could represent a sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 227 publications
(572 reference statements)
2
46
0
Order By: Relevance
“…Seagrass holobionts have been reported to play essential roles in the cycle of sulfur, nitrogen, and carbon, at both microbial structural and functional levels [ 11 , 13 ], and Ugarelli et al (2019) [ 51 ] reported that the seagrass plant and its microbiome were highly interlinked in the cycle of sulfur, nitrogen, and carbon. Likewise, FAPROTAX analysis revealed that many microbes in the seagrass rhizosphere of coral reef ecosystems participated in these processes ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seagrass holobionts have been reported to play essential roles in the cycle of sulfur, nitrogen, and carbon, at both microbial structural and functional levels [ 11 , 13 ], and Ugarelli et al (2019) [ 51 ] reported that the seagrass plant and its microbiome were highly interlinked in the cycle of sulfur, nitrogen, and carbon. Likewise, FAPROTAX analysis revealed that many microbes in the seagrass rhizosphere of coral reef ecosystems participated in these processes ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…FAPROTAX dataset is a manually constructed database that maps prokaryotic taxa (e.g., genera or species) to putative functions based on the literature on cultured representatives [ 40 ]. The core microbial community in this study was defined as those present in all samples, including all three replicates [ 11 ], and their network analysis was further analyzed based on a random matrix theory (RMT)-based method according to Deng [ 41 ] and Luo [ 42 ]. Network analysis of the core microbial community was processed using by molecular Ecological Network Analysis Pipeline ( (accessed on 17 August 2020)) and visualized in an open-source software platform Cytoscape (v.3.6.0).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations